An I(I)/I(III) Catalysis Route to the Heptafluoroisopropyl Group: A Privileged Module in Contemporary Agrochemistry - Martín-Heras, Víctor; Daniliuc, Constantin G.; Gilmour, Ryan (Synthesis, 2021)
The heptafluoroisopropyl group is emerging as a privileged chemotype in contemporary agrochemistry and features prominently in the current portfolio of leading insecticides. To reconcile the expansive potential of this module with the synthetic challenges associated with preparing crowded, fluorinated motifs, I(I)/I(III) catalysis has been leveraged. Predicated on in situ generation of p-TolIF2, this route enables the direct difluorination of α-trifluoromethyl-β-difluorostyrenes in a single operation. This formal addition of fluorine across the alkene π-bond is efficient (up to 91% yield) and is compatible with a broad range of functional groups. The ArCF(CF3)2 moiety is conformationally preorganised, with the C(sp3)–F bond coplanar to the framework of the aryl ring, thereby minimising 1,3-allylic strain. Moreover, orthogonal multipolar C–F···C=O interactions have been identified in a phthalimide derivative. It is envisaged that this programmed vicinal difluorination enabled by a hypervalent iodine species will find application in functional molecule design in a broader sense.
Keywords: agrochemistry; catalysis; conformational analysis; fluorine; hypervalent iodine; vicinal oxidation